Analysis of the Impact Toughness of Boehmeria Nivea Fiber-Reinforced Composites with UHMWPE Matrix as Potential Biomaterials - Rafsanjanu, Swastika Pascal; Hastuti, Sri; Hilmy, Fuad; Saputra, Eko; Nugroho, Wahyu Isti; Putri, Farika Tono; Indrawati, Ragil Tri (Jurnal Rekayasa Mesin, 2025)
Bone implants are generally made of metal materials that have the strength and toughness to fuse broken or fractured bones, but they have the disadvantage of causing pain due to the metal's ability to absorb ambient temperatures and the relatively high cost of implant materials. Therefore, Ultra High Molecular Weight Polyethylene (UHMWPE) reinforced with hemp fiber is needed. This study aims to analyze impact toughness and observations on fracture cross-sections. This study uses a composite of hemp fiber (SR) with a UHMWPE (UP) matrix, which will be made using the hot press method. The research method used is an experimental method to determine the effect of adding material mixtures by varying the volume fraction of the composite fiber. The volume fraction variations used included 3% SR: 97% UP, 5% SR: 95% UP, and 7% SR: 93% UP. The test specimens referred to the ASTM D5942 standard for impact testing. The impact test results showed that the highest impact toughness value was 0.0514 J/mm2 in the 3%SR : 97%UP variation and the lowest impact toughness value was 0.0478 J/mm2 in the 7%SR : 93%UP variation.  SEM observations of the fracture cross-section revealed failures caused by fiber pull-out, debonding, and matrix cracking.